Religious Hatred and Byzantine Ideology before the Crusades - ROTMAN, Youval (Byzantina Symmeikta, 2022)
Religious hatred has a long and painful history. It was conceptualized, defined and employed in various ways and for various ends throughout history. The present article focuses on the religious hatred and the roles that it played in Byzantium. It proposes a comparative approach to analyze expressions of religious hatred in Byzantine texts. The article does not analyze religious hatred as the actual hatred that a Christian might feel for his Jewish neighbor because he is Jewish, or vice-versa, but the way it appears in texts as a literary and rhetorical construction. What could be termed “Byzantine typology of religious hatred” as it presented and constructed in different types of texts by different authors will reveal the construction of a Byzantine perspective to mark political enemies as religious adversaries and vice versa. The question is to what end. This article proposes to look more closely into the way religious hatred served as a tool in the construction of Byzantine public opinion, a means for the Byzantines to perceive their polity and themselves as righteous.